Morphological investigations on the growth of defect-rich Bi2Te3 nanorods and their thermoelectric properties. Issue 33 (27th July 2018) - M, Sinduja; Amirthapandian, S.; Jegadeesan, P.; Magudapathy, P.; Asokan, K.
Abstract : Bi2 Te3 nanorods (NRs) have been successfully synthesized at different reaction temperatures via a surfactant-assisted hydrothermal method. Abstract : Bi2 Te3 nanorods (NRs) have been successfully synthesized at different reaction temperatures via a surfactant-assisted hydrothermal method. The experimental observations revealed that the reaction temperature, SDBS surfactant (sodium dodecylbenzene sulphonate) and its concentration affect the morphology of Bi2 Te3 . It is identified that an imperfect oriented attachment mechanism is the dominant growth mechanism for the evolution of Bi2 Te3 NRs. Moreover, a subsidiary growth mechanism namely the Oswald ripening process could also affect the Bi2 Te3 NR growth process at higher reaction temperatures. Thermoelectric property measurements revealed that flake-decorated Bi2 Te3 NRs achieved the maximum power factor value of ∼1.32 μW cm −1 K −2 at 410 K, which was higher than those of porous and smooth Bi2 Te3 NRs. Such an enhancement in the power factor of flake-decorated Bi2 Te3 NRs is primarily attributed to their outstanding electrical conductivity at 410 K.